Alternative polyadenylation of antisense RNAs and flowering time control. (26th July 2010) - Hornyik, Csaba; Duc, Céline; Rataj, Katarzyna; Terzi, Lionel C.; Simpson, Gordon G.
Abstract : Flowering time is controlled by precision in gene regulation mediated by different pathways. Two Arabidopsis thaliana components of the autonomous flowering pathway, FCA and FPA, function as genetically independent trans -acting regulators of alternative cleavage and polyadenylation. FCA and FPA directly associate with chromatin at the locus encoding the floral repressor FLC, but appear to control FLC transcription by mediating alternative polyadenylation of embedded non-coding antisense RNAs. These findings prompt the re-examination of how other factors control FLC expression, as it is formally possible that they function primarily to control alternative processing of antisense RNAs. As co-expressed sense and antisense gene pairs are widespread in eukaryotes, alternative processing of antisense RNAs may represent a significant form of gene regulation.